EFFECT OF BORON ON THE WEAR BEHAVIOR OF HIGH CHROMIUM WHITE CAST IRONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The wear behavior of high chromium white cast irons with composition: 2,6÷3,4% C; 0,9÷1,1% Si; 0,8÷1,1% Mn; 1,0÷1,3% Mo; 12,3÷13,4% Cr and 0,18 ÷ 1,25% B is investigated. The microstructure and tribological characteristics of six compositions of high chromium white cast irons (one without boron and with 0,18; 0,23; 0,59; 0,96; 1,25% boron) are studied.After casting, heat treatment was carried out, including quenching at 9500C and tempering at 2350C for 1 h. The influence of the heating temperature in the interval 850÷11000С, 25 min on the Rockwell hardness and the microstructure are studied.The wear resistance during abrasive wear for samples after casting and after heat treatment is investigated as measured loss of mass in terms of dry friction under load of 1,5 kg during 10 min. The lowest mass loss during abrasive wear test in dry conditions friction is defined for cast irons alloyed with 0,18 % boron - ∆ m = 0,1469 g after casting and ∆ m = 0,0022 g after heat treatment. The highest mass loss is determined during abrasive testing of alloyed cast irons with 0,96 and 1,25% boron. The alloyed cast irons with 0,18 % boron show highest wear resistance.